2016
DOI: 10.5114/pm.2016.65667
|View full text |Cite
|
Sign up to set email alerts
|

PARP inhibitors: review of mechanisms of action and BRCA1/2 mutation targeting

Abstract: Poly(ADP-ribose) polymerases have shown true promise in early clinical studies due to reported activity in BRCA-associated cancers. PARP inhibitors may represent a potentially important new class of chemotherapeutic agents directed at targeting cancers with defective DNA-damage repair. In order to widen the prospective patient population that would benefit from PARP inhibitors, predictive biomarkers based on a clear understanding of the mechanism of action are required. In addition, a more sophisticated unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
126
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(129 citation statements)
references
References 31 publications
1
126
0
2
Order By: Relevance
“…To restore cellular NAD + levels and thus counteract detrimental pathways, inhibition of NAD + ‐consuming enzymes, most notably poly(ADP‐ribose)polymerase 1 (PARP1) and CD38/CD157, has shown promise . The significance of NAD + ‐mediated processes necessitates the development of new tools and probes to facilitate biophysical analyses and the fabrication of effective discovery assays.…”
Section: Introductionmentioning
confidence: 99%
“…To restore cellular NAD + levels and thus counteract detrimental pathways, inhibition of NAD + ‐consuming enzymes, most notably poly(ADP‐ribose)polymerase 1 (PARP1) and CD38/CD157, has shown promise . The significance of NAD + ‐mediated processes necessitates the development of new tools and probes to facilitate biophysical analyses and the fabrication of effective discovery assays.…”
Section: Introductionmentioning
confidence: 99%
“…Poly ADP ribose polymerase inhibitors (PARPi) are presently approved as maintenance therapy following platinum and taxol chemotherapy. PARPi function by blocking PARP1 protein, inducing synthetic lethality in HGSOC containing mutations in genes involved in the homologous recombination pathway of DNA repair (HR) . Olaparib was the first PARPi to be introduced as a maintenance treatment for ovarian cancer patients …”
Section: Introductionmentioning
confidence: 99%
“…And it is also suggested that defective HR secondary to BRCA1 and BRCA2 mutations may render cancer cells particularly sensitive to inhibition of singles stranded binding proteins (SSB) repair through inhibition of PARP [17]. Particularly, PARP inhibitors such as olaparib and niraparib exhibited significant antitumor efficacy in ovarian, breast, and PCa with dysfunctional HR [18]. Moreover, these are being extensively investigated in multiple clinical trials.…”
Section: Therapeutic Significance Of Dna Mismatch Repair In Prostate mentioning
confidence: 99%